Modelo de cistite hemorrágica induzida por injeção intravesical de acroleína : efeito uroprotetor de compostos tióis (mesna, glutationa e amifostina) - Batista, Cristina Kelma Loiola Ponte (2002)
Acrolein (ACR) is a highly reactive and toxic aldehyde produced as a metabolic urinary product of the anticancer drugs Cyclophosphamide (CYP) and Ifosfamide (IFO) that was related as the causative agent of Hemorrhagic Cystitis (HC) induced by these compounds. Systemic administration of CYP or IFO would induce HC through the release of ACR. However, a possible direct effect of ACR to the urothelium is yet to be demonstrated. In this study we aimed to evaluate the effects of the local intravesical (i.ve.) injection of ACR to mice, as well as the cytoprotective action of the thIol compounds: Mesna, the classical ACR chemical antagonist; the reduced form of the endogenous thiol Glutathione (GSH), and Amifostine (AMF), an agent that selectively protects normal tissues against a wide variety of toxic effects induced by anticancer chemotherapy. Male Swiss mice received ACR (25, 75, or 225 mg) i.ve. - 3, -6, -12 or -24 h before sacrifice. the increase in vascular permeability (VP) in the bladders was evaluated by the measure of the concentration of Evans blue dye extravasation, injected 30 min before ACR (25mg/kg e.v.) and by comparison of the Bladder Wet Weight between the groups. The macroscopical and histopathologycal changes were evaluated using the Gray’s criteria. Groups received local (i.ve.) Mesna (2mg), GSH (2mg) or AMF(1,5mg) or systemic (i.p.) Mesna (80 mg/kg), GSH (125,250,500 mg/Kg), and AMF(25,50,100 mg/Kg) 30 min before ACR. Local ACR induced a dose and time-dependent increase in bladder edema as well as in the macroscopical and histopathological lesions, that was significantly different from controls, being maximal 12 h after ACR injection (p<0.05). Pretreatment with either Mesna, GSH, or AMF inhibited both the edema, macroscopical and the histopathological changes, regardless of local or systemic adminstration. This protective effect of the thiol compounds was also demonstrated in HC induced by IFO (400 mg/Kg ip). In conclusion, our results confirmed the role of ACR in the genesis of HC induced by oxazaphosphorines and indicated the thiol compounds as an important celular defense line in this pathological condition.